(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
In the present study, the edible portions of whole fish excluding viscera and bone of five different freshwater fish species samples are analysed for lead, manganese, nickel, zinc, copper and iron by atomic absorption spectrophotometry (AAS). The relative standard deviations (RSD) were found below 5%. The accuracy of the methods was confirmed by certified reference materials. The concentrations of trace elements in the edible portions of other fish comply with the international standards for human consumption. Key words: Trace element; Gumti river; Freshwater fish; Atomic absorption spectrophotometry (AAS); Metal contamination DOI: http://dx.doi.org/10.3329/bjsir.v46i1.8101 Bangladesh J. Sci. Ind. Res. 46(1), 27-32, 2011